The nocebo effect and its relevance for clinical practice - Colloca, Luana (2011)
Negative expectations deriving from the clinical encounter can produce negative outcomes, known as nocebo effects. Specifically, research on the nocebo effect indicates that information disclosure about potential side effects can itself contribute to producing adverse effects. Neurobiological processes play a role in the nocebo effect and this paper provides a selective review of mechanistic research on the nocebo effect. Comparatively little attention has been directed to clinical studies and their implications for daily clinical practice. The nocebo response is influenced by the content and the way information is presented to patients in clinical trials in both the placebo as well as active treatment conditions. Nocebo effect adversely influences quality of life and therapy adherence, emphasizing the need for minimizing these responses to the extent possible. Evidence further indicates that the informed consent process in clinical trials may induce nocebo effects. This paper concludes with ethical directions for future patient-oriented research and routine practice.